2017
DOI: 10.1098/rspb.2017.0897
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic development of sensory structures in brains of diapausing butterfly pupae: implications for information processing

Abstract: Diapause is an important escape mechanism from seasonal stress in many insects. A certain minimum amount of time in diapause is generally needed in order for it to terminate. The mechanisms of time-keeping in diapause are poorly understood, but it can be hypothesized that a well-developed neural system is required. However, because neural tissue is metabolically costly to maintain, there might exist conflicting selective pressures on overall brain development during diapause, on the one hand to save energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…We did not detect pulses, or waves of gene expression at the whole-CNS level that are often associated with metamorphosis (61) and neurogenesis (60), although such patterns may be present in specific neuron subtypes or may have been obscured by interindividual variation within our sampling pools. Gross CNS morphology did not change during 6 mo of diapause, a pattern also observed based on fineresolution imaging of brain substructures over time in diapausing butterfly pupae (62). However, the overall signal of development in the transcriptomic data, for example up-regulation of cell fate proteins associated with cell differentiation, and many transcripts associated with neurogenesis, is most consistent with some sort of developmental progression.…”
Section: Cns Transcriptome Trajectories Show Widespread Evolutionarysupporting
confidence: 59%
See 1 more Smart Citation
“…We did not detect pulses, or waves of gene expression at the whole-CNS level that are often associated with metamorphosis (61) and neurogenesis (60), although such patterns may be present in specific neuron subtypes or may have been obscured by interindividual variation within our sampling pools. Gross CNS morphology did not change during 6 mo of diapause, a pattern also observed based on fineresolution imaging of brain substructures over time in diapausing butterfly pupae (62). However, the overall signal of development in the transcriptomic data, for example up-regulation of cell fate proteins associated with cell differentiation, and many transcripts associated with neurogenesis, is most consistent with some sort of developmental progression.…”
Section: Cns Transcriptome Trajectories Show Widespread Evolutionarysupporting
confidence: 59%
“…Such an evolutionary innovation would represent an extreme analog of the well-documented phenomenon of substantial variation in the duration of all individual life cycle stages across Insecta ( 65 ). Indeed, the developmental steps during CNS metamorphosis are indistinguishable between direct developing and diapausing pupae of the butterfly Pieris napi ( 62 ). Moreover, measurable morphogenesis seems to occur during diapause in other insects, particularly gonadal development during adult reproductive diapause ( 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lehmann et al. () demonstrated that in the butterfly Pieris napi (L.), the sensory structures linked to vision are well developed in pupae in diapause, unlike other cerebral structures. These results, although preliminary, suggest that these structures may play a role in maintaining and terminating diapause (Lehmann et al., ).…”
Section: Pursuing Studies On Diapausementioning
confidence: 99%
“…In insects, neural mechanisms associated with the detection of photoperiodism could be involved in measuring the amount of time elapsed since the onset of diapause (Saunders, 2012). Recently, Lehmann et al (2017a) demonstrated that in the butterfly Pieris napi (L.), the sensory structures linked to vision are well developed in pupae in diapause, unlike other cerebral structures. These results, although preliminary, suggest that these structures may play a role in maintaining and terminating diapause (Lehmann et al, 2017a).…”
Section: Diapause Expression In a Climate Change Contextmentioning
confidence: 99%
See 1 more Smart Citation